Evolutionary insights into the Andean genus Nicandra (Solanoideae, Solanaceae) - Seculin Glur, Julieta L.; Gutiérrez Nicolás, Fátima; Leiva González, Segundo; Barboza, Gloria E.; Carrizo García, Carolina (Phytotaxa, 2022)
Nicandra (Solanaceae) is a small Andean genus, historically considered monospecific, with N. physalodes as its only species. This species is native to the South American Andes but naturalized in many countries worldwide. Recently, N. john-tyleriana and N. yacheriana were described using morphological evidence, which are endemic to Peru. Sequence data from four DNA markers, the plastidial intergenic spacers trnL-trnF and ndhF-rpl32, and the nuclear ITS region and GBSSI (waxy) gene, were used to test the identity of the nominal species using genomic evidence, to reconstruct the genus phylogenetic history through Maximum Likelihood and Bayesian Inference, and to estimate divergence times within the genus. The three Nicandra species formed distinct partitions and monophyletic lineages. Nicandra physalodes, originated in the late Miocene (ca. 8 My), was resolved as the first splitting branch, sister to the siblings N. john-tyleriana and N. yacheriana, which were originated at the end of the Miocene (ca. 5 My). The crown ages for the three species were estimated from the early Pliocene (N. physalodes) to the mid-Pleistocene (N. john-tyleriana and N. yacheriana), which is consistent with hypotheses of Neotropical species diversification. Open questions remain about the biogeography of the genus.